An analysis of competencies and moderating influence of demographic profiles - Evidence from exporting organizations - Kuppusamy, Jayanty; Anantharaman, Reddiyoor Narayanaswamy (IBIMA Publishing, 2008)
The increasing numbers of organizations involved in exporting intensifies the competition level. Therefore, to manage the competition effectively, organizations need the necessary competencies. The objective of the study is to determine the relationship between competencies and export performance. The competencies tested are in the area of personal traits, management, production and marketing. The results showed that except for personal traits, all the competencies have an influence on export performance. Demographic characteristics (key decision makers' demographics and organizational demographics) art, also tested to identify whether they have moderating effects on the relationship between competencies and export performance. These include key decision makers' demographics (age, education, overseas exposure and employment experience) and organizational demographics (age, size of organization and export experience). The result showed age and education (key decision maker's demographics) have an effect in the relationship between competencies and export performance. However, all the organizational demographics tested have a moderating effect.